2014
DOI: 10.1002/cpp.1917
|View full text |Cite
|
Sign up to set email alerts
|

Is It All about the Higher Dose? Why Psychoanalytic Therapy Is an Effective Treatment for Major Depression

Abstract: Psychoanalytic therapy is an effective treatment for major depression, especially in the long run. The differential effectiveness of psychoanalytic therapy cannot be fully explained by its higher dose. Distinctive features of psychoanalytic technique (e.g., focusing on patients' dreams, fantasies, sexual experiences or childhood memories) may play an important role in establishing sustained therapeutic change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 77 publications
(117 reference statements)
1
38
0
14
Order By: Relevance
“…We have previously found that punitive and harsh self-introjects change more in LTG than STG [9]. Recent studies comparing psychodynamic therapies of different length and intensity indicated that long-term therapy was more favourable than short-term therapy with regard to depression and interpersonal functioning [2,3,8,10]. …”
Section: Figmentioning
confidence: 99%
“…We have previously found that punitive and harsh self-introjects change more in LTG than STG [9]. Recent studies comparing psychodynamic therapies of different length and intensity indicated that long-term therapy was more favourable than short-term therapy with regard to depression and interpersonal functioning [2,3,8,10]. …”
Section: Figmentioning
confidence: 99%
“…These interaction patterns allow the clearest insight into transference-countertransference dynamics in the therapeutic relationship. De Bei & Montrosi (2013) claim, in line with Jones (2000), that the therapist's and patient's experience, recognition and understanding of these recursive interactions should be linked to therapeutic interventions and compared to the mediating effects of analytic techniques (Zimmermann et al 2014).…”
Section: Dimensions Of Activity In Countertransference and Therapist mentioning
confidence: 87%
“…Therefore, the core of this paper lies in identifying the dimensions of how therapists feel and react during the sessions in general. Zimmermann et al (2014) for instance, found support for the mediating effect of psychoanalytic techniques, namely working with countertransference reactions to predict projective identification, hypothesizing that with depressed patients, favourable long term trajectories of depressive symptoms could be achieved. These findings are in line with previous studies (Ablon & Jones 1998;Gaston et al 1998;Hilsenroth et al 2003) and extend them by showing that psychoanalytic therapies are effective.…”
Section: Dimensions Of Activity In Countertransference and Therapist mentioning
confidence: 99%
See 1 more Smart Citation
“…B. die Metaanalyse von Vittengl et al [8] [9]. Die Nachhaltigkeit wurde von den Autoren auf die deutlich stär-kere Therapiedosis zurückgeführt [10]. In einer RCT [11] konnte im Langzeitverlauf nach drei Jahren eine signifikant stärkere Reduktion der depressiven Symptomatik in einer psychodynamischen Langzeittherapie im Vergleich zu einer systemisch-lösungsorientierten Kurzzeittherapie gezeigt werden, während im Selbstrating nach drei und sieben Monaten nach Therapiebeginn signifikant stärkere Reduktionen sowie höhere Remissionsraten nach sieben bis zwölf Monaten bei systemisch-lösungsorien-tierter Kurzzeittherapie auftraten.…”
Section: Längerfristige Stabilisierende Psychotherapie (Rezidivprophyunclassified